PEMANFAATAN CERPEN SEBAGAI MEDIA PEMBELAJARAN MENULIS DI KELAS XI TINGKAT SMK - Desnila Sari (Institut Binamadani Indonesia, 2021)
Students are active learners and creative, contextual learning to recognize the identity and act based on their interests, performing and interacting with the environment and study the system of meaning. Various learning to write in class XI vocational level indicates that it was found that students encounter conditions that are not in line with their needs. As a result of learning media is still limited, students are not getting the conditions for active and creative to be a writer. This journal is made ​​to find an alternative solution to the problem of limited media use as a medium of learning to write short stories in class XI vocational level. Once implemented learning, students tend to be more active and creative in learning to write. The ability of students increased after the media used by the teacher As with learning media. The conclusion of this paper is that: (1) short story the media can be a solution to overcome the problem of learning to write in class XI vocational level, (2) media stories help teachers to improve students' skills in more active and creative writing, and (3) media stories to develop students to be active and creative writer.